Impact Analysis of Gig Economy on Traditional Labour Structure - Judijanto, Loso; Caroline, Caroline; Andhiyan Mergining Mei, Nanang (Lafadz Jaya Publisher, 2025)
The growth of the gig economy in Indonesia has triggered significant transformations in the traditional labour structure. This study aims to analyse the impact of the gig economy on workers' employment patterns, income, and social protection using a literature review method. The results of the analysis show that the gig economy offers flexibility and new employment opportunities but also increases income uncertainty and widens the social protection gap between gig and traditional workers. In addition, there is a skills disruption that requires increased digital literacy and worker adaptability. This research recommends the need for labour regulation reform, strengthening portable social security systems, and expanding access to digital training so that the gig economy can provide inclusive and sustainable benefits for the entire Indonesian workforce.